The Influence Of Physical Evidence, Reliability, Responsiveness, Assurance And Empathy To The Consumer Satisfaction Of The Kfc Grand Kota Bintang Bekasi - Waseso Segoro; Maria Magdalena Tri Permatasari (Publisher Cv. Inara, 2021)
The growing number of fast-food restaurants, which allow businesses to compete with one another to meet their business goals and to provide good quality services so that they can provide individual satisfaction for their consumers. The study was intended to identify the effects of physical evidence, reliability, responsiveness, assurance and empathy to the consumer satisfaction of the KFC Grand Kota Bintang Bekasi.The analysis tools used in this study are validity test, reliability test, normality test, multicollity test, linear regression test, t-test (partial trials), f-test (simultaneous tests) and coefficiencies tests using version SPSS22. The data used is primary data collected through the questionnaires’ method of disseminating the 100 consumer KFC Grand Kota Bintang Bekasi.Research suggests that partial evidence, reliability responsiveness can significantly affect consumer satisfaction while partial assurance and empathy do not significantly affect consumer satisfaction. And simultaneously physical evidence, reliability, responsiveness, assurance and empathy affect significantly the consumer satisfaction of the KFC Grand Kota Bintang Bekasi.